La alienación parental como componente valoratorio al régimen de visitas abiertas. - Baños Angamarca Javier Alexander (2025)
The present research aims to analyze parental alienation as a key evaluative component in determining the open visitation regime. Parental alienation, defined as the process by which one parent negatively influences the child’s perception of the other parent, has become a frequent phenomenon in divorce or child custody disputes. This type of manipulation severely affects the emotional and psychological well-being of children and adolescents, violating their fundamental rights, such as the right to identity, the right to know and maintain a relationship with both parents, and the right to emotional stability. The proposed legal analysis is framed within the principle of the Best Interests of the Child, established in the Constitution of the Republic and the Organic Code of Childhood and Adolescence. It focuses primarily on delving doctrinally and legally into how parental alienation can and should be considered by judges when assessing the suitability of the open visitation regime, prioritizing the comprehensive development of children and adolescents, their rights to protection, and, above all, the guiding principles concerning childhood and adolescence. The core of this research revolves around the requirements for optimal conditions to resolve the concept of flexible visitation, as it is essential to ensure no harm is caused to the minor. Through an interdisciplinary approach combining elements of law, psychology, and family mediation, this study proposes that detecting and preventing parental alienation in judicial processes is vital to guaranteeing fairer and more balanced decisions that prioritize the child’s overall well-being. 5 This analysis is significant because the process of discrediting the non-custodial parent, used as a retaliatory tool, severely violates the rights of the child, deteriorating their emotional and psychological stability. Additionally, it deprives the child of a harmonious relationship with the alienated parent, which is illegal and contradicts fundamental principles of childhood and adolescence law, even infringing on essential rights such as identity, the right to know and maintain relationships with both parents, the right to be consulted on decisions affecting them, and family coexistence. Collectively, this constitutes a violation of the principle of the Best Interests of the Child, enshrined both in the Constitution of the Republic and the Organic Code of Childhood and Adolescence, which recognizes children and adolescents as a vulnerable population group. The research employs a descriptive and analytical methodology, reviewing both current Ecuadorian regulations and relevant jurisprudence, in addition to incorporating psychological studies on the effects of parental alienation. Based on these inputs, conclusions are drawn, and recommendations are formulated to improve the regulation of the open visitation regime, emphasizing the importance of protecting the rights of minors against parental manipulation and promoting a healthy family environment. Keywords: Parental Alienation, Open Visitation Regime, Comprehensive Protection, Best Interests of the Child, Evaluative Component, Principles, Rights.